69: Identifying Risk Factors for Unplanned Extubations in the NICU: Laying the Groundwork for a Quality Improvement Initiative. Issue 5 (1st June 2015) - Hewitt, M; Sproul, E; Emberley, J
Abstract: BACKGROUND: Unplanned extubations (UEs) are a common adverse event experienced by ventilated neonates in the Neonatal Intensive Care unit (NICU) and can lead to significant morbidity in an already vulnerable population. Despite the fact that UEs are increasingly recognized as an important quality of care metric, this adverse event was not being routinely reported at our institution. We sought to determine the rate of UEs in this NICU and identify risk factors to target future quality improvement interventions. OBJECTIVES: 1. To determine the rate of UEs (# of UEs/100 ventilator days) in a level II/III NICU; 2. To identify risk factors associated with UEs. DESIGN/METHODS: Institutional ethics approval was obtained prior to start of the study. A retrospective chart review was conducted for all intubated neonates admitted to a 34 bed level II/III NICU from January 1st, 2013 until December 31st, 2013. An UE was defined as any removal of an endotracheal tube not directly ordered or intended by a physician. For each UE event, the following data were collected: gestational age, birth weight, gender, weight at time of extubation, time at which event occurred, reason for extubation, and total number of ventilation days. UE rate was calculated by #UEs/100 ventilator days. Reasons for UEs were expressed by Pareto charting. Multivariate regression analysis was performed for gestational age, birth weight, and total ventilation time. Timing of event was categorized as either day or night shift and analyzed for significance using ANOVA. RESULTS: The UE rate was 3.28 UEs/100 ventilator days. Patient movement and adhesive failure accounted for over 50% of UEs. In 22.7% of cases, patients did not require re-intubation. Total ventilation time was the only statistically significant risk factor for UEs with a 7.3% increased risk per ventilation day past the mean. UEs were no more likely to occur on day versus night shift, nor were there any significant differences in the reasons for UE based on shift. CONCLUSION: The UE rate at this institution was higher than the suggested benchmark. More than 20% of patients did not require reintubation, reinforcing the need for more aggressive weaning protocols. Interestingly, night versus day shift was not found to be a significant risk factor. Total ventilation days independently predicted UE risk; pre-emptively identifying such patients is a potential avenue for future quality improvement interventions.